2017
DOI: 10.1016/j.ejogrb.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent endometriosis

Abstract: Endometriosis is a common finding in adolescents who have a history of chronic pelvic pain or dysmenorrhoea resistant to medical treatment, however the exact prevalence is unknown. Both early/superficial and advanced forms of endometriosis are found in adolescents, including ovarian endometriomas and deep endometriotic lesions. Whilst spontaneous resolution is possible, recent reports suggest that adolescent endometriosis can be a progressive condition, at least in a significant proportion of cases. It is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…In line with the results of this thesis (study III), women with endometriosis scored significantly lower than controls on SF-36, with young women having the worst HRQoL [116]. The management of adolescent endometriosis is known for its unique challenges, with diverse and sometimes diffuse symptoms and prolonged diagnostic delay [117,118]. Specific structural and process-related strategies aimed at finding and helping these young women at an early age should be considered in the work towards strengthening the quality of endometriosis care.…”
Section: "Pain-focused" Versus "Disease-focused" Endometriosis Caresupporting
confidence: 73%
“…In line with the results of this thesis (study III), women with endometriosis scored significantly lower than controls on SF-36, with young women having the worst HRQoL [116]. The management of adolescent endometriosis is known for its unique challenges, with diverse and sometimes diffuse symptoms and prolonged diagnostic delay [117,118]. Specific structural and process-related strategies aimed at finding and helping these young women at an early age should be considered in the work towards strengthening the quality of endometriosis care.…”
Section: "Pain-focused" Versus "Disease-focused" Endometriosis Caresupporting
confidence: 73%
“…This inconsistent observation could be due in part to the differences in endometriosis phenotype and age range of the study participants. Prior studies reported CA125 does not perform as well in detecting minimal to mild endometriosis (rASRM stage I/II) [ 30 32 ], which is known to be the predominant clinical phenotype of adolescent endometriosis [ 14 , 33 , 34 ]. Furthermore, the average age of endometriosis cases in one prior study was 34 while the average age in our endometriosis cases was 19.6.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incidence of endometriosis in the paediatric population increases significantly from 5% to 40% in the presence of defects in the reproductive organs resulting from congenital anomalies in the development of the Mullerian ducts, leading to obstruction of the reproductive organ and disturbance of menstrual drainage [ 79 , 83 , 88 ]. Laparoscopy is the gold standard in the assessment of endometriosis, and in accordance with the guidelines of the American College of Obstetricians and Gynaecologists (ACOG) of 2018 it should be used in the case of persistent pain despite the use of cyclic two-component contraceptive therapy and NSAIDs for a period of 3 months [ 83 , 89 ]. Therefore, laparoscopy is the last diagnostic stage in chronic pelvic pain in the paediatric population.…”
Section: Endometriosismentioning
confidence: 99%